Affective and Behavioral Features of Jealousy Protest: Associations with Child Temperament, Maternal Interaction Style, and Attachment. (5th April 2012) - Hart, Sybil L.; Behrens, Kazuko Y.
<x xml:space="preserve">Abstract</x> This study explored variation in affective and behavioral components of infants' jealousy protests during an eliciting condition in which mother and an experimenter directed differential attention exclusively toward a rival. Variation was examined in relation to child temperamental emotionality, maternal interaction style, and attachment security. At 45 weeks, intensity of infants'distress and durations of mother‐ and stranger‐directed behavioral responses, including gaze, touch, and proximity‐seeking, were observed in the eliciting condition. We also assessed infants'positive emotionality (PE) and negative emotionality (NE) and maternal interaction styles of sensitivity and engagement. At 54 weeks, attachment security was measured in the Strange Situation Procedure. Findings revealed that distress differed with temperamental emotionality and maternal interaction style. Specifically, distress was greater in infants with lower PE and having mothers who displayed less sensitivity and engagement. Analyses on behavioral responses toward the experimenter revealed linkages with maternal interaction style. Specifically, experimenter‐directed gaze and touch were greater among infants of mothers who demonstrated less sensitivity and engagement. Behavioral responses toward mother were found associated with quality of attachment. Specifically, mother‐directed proximity and touch were highest among infants later judged insecure resistant and lowest among those later judged insecure/avoidant; with infants later judged secure displaying moderate durations of mother‐directed proximal contact.